Tracing insular woodiness in giant Daucus (s.l.) fruit fossils from the Early Pleistocene of Madeira Island (Portugal). Issue 6 (14th January 2020) - Góis‐Marques, Carlos A.; de Nascimento, Lea; Fernández‐Palacios, José María; Madeira, José; Menezes de Sequeira, Miguel
Abstract: Plants on oceanic islands can evolve insular syndromes such as secondary woodiness, a generalized trend found in island floras worldwide. This phenomenon occurs through evolution in situ . It is triggered by ecological and physiological stimuli that transform herbaceous annuals into woody perennials. However, well‐dated and informative fossils that could help track and frame the evolution of this syndrome are lacking. Remarkably, in Madeira Island (Portugal), there are good examples of Apiaceae that evolved secondary woodiness, like the giant neoendemic Melanoselinum (≡ Daucus ). Apiaceae has a very scarce fossil record, despite being a cosmopolitan family and an economically important crop. Here we describe the oldest Daucus s.l. fossil known to date and the first fossil evidence of a plant with insular woodiness. The fossils are preserved as mummified/compressed mericarps within 1.3‐million‐year‐old fluvio‐lacustrine sediments of the Funchal unit, Upper Volcanic complex, near Porto da Cruz. We assign them to the extant neoendemic species Melanoselinum (≡ Daucus ) decipiens . The mericarp morphology shows remarkable stasis since the Calabrian stage of the Early Pleistocene. Our results demonstrate that in the Madeiran Daucinae clade, insular woodiness developed at least 1.3 million years ago, indicating a coeval or earlier immigration to Madeira Island of a Daucus sp. Our results reinforce the role of palaeobotanical research in oceanic islands, supported by stratigraphy and geochronology studies, as a key element for the understanding of plant palaeobiogeography, ecology and evolution worldwide. We expect this contribution to shed light on the evolutionary origins of carrots, and related plant groups, an important element of human food, and to better comprehend the evolution of plant insular woodiness.